2021
DOI: 10.3390/ma14205949
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar Brazing of Ti–15Mo–5Zr–3Al and Commercially Pure Titanium Using Ti–Cu–Ni Foil

Abstract: Dissimilar brazing of Ti–15Mo–5Zr–3Al (Ti-1553) to commercially pure titanium (CP-Ti) using Ti–15Cu–15Ni foil was performed in this work. The microstructures in different sites of the brazed joint showed distinct morphologies, which resulted from the distributions of Mo, Cu, and Ni. In the brazed zone adhered to the Ti-1553 substrate, the partitioning of Mo from the Ti-1553 into the molten braze caused the formation of stabilized β-Ti without Ti2Cu/Ti2Ni precipitates. In the CP-Ti side, the brazed joint displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It was concluded that strength of the joint primarily depends on the microstructure formed in the brazing zone and the formation of intermetallics in the joint area. β-Titanium alloy (Ti-15Mo-5Zr-3Al) was brazed to commercial pure Titanium by Gui-Lin Yue et al 19 using Ti-Cu-Ni filler alloy foil. It was done at 1243 K for different brazing time durations of 3, 30 and 60 min, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that strength of the joint primarily depends on the microstructure formed in the brazing zone and the formation of intermetallics in the joint area. β-Titanium alloy (Ti-15Mo-5Zr-3Al) was brazed to commercial pure Titanium by Gui-Lin Yue et al 19 using Ti-Cu-Ni filler alloy foil. It was done at 1243 K for different brazing time durations of 3, 30 and 60 min, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have experimented with brazing commercial Titanium and Titanium alloys using Ti-based filler metals 19,20 . It was concluded that strength of the joint primarily depends on the microstructure formed in the brazing zone and the formation of intermetallics in the joint area.…”
Section: Introductionmentioning
confidence: 99%